PO.6.137 Design of a phase 2, multicenter, randomized, placebo-controlled, parallel-group, double-blind study to assess the efficacy and safety of nipocalimab in adults with active systemic lupus erythematosus. (27th September 2022) - Liu-Walsh, F; Van Hartingsveldt, B; Zuraw, Q; Hoffman, RW; Rooney, T; Gao, S; Gordon, R; Leu, JH; Berhanu Debella, A; Calderon, C; Zazzetti, F; Vratsanos, G
Abstract : Objective: Systemic lupus erythematosus (SLE) is a chronic, complex autoimmune disease characterized by pathogenic autoantibodies and tissue damage to multiple organ systems. Approved treatments are few and associated with limitations including suboptimal response for many patients. Nipocalimab is a novel high affinity, fully human, aglycosylated, effectorless IgG1 monoclonal antibody that selectively targets the neonatal Fc receptor (FcRn). Clinical studies conducted with nipocalimab in healthy volunteers (NCT02828046 ) and in adult generalized myasthenia gravis patients (NCT03896295 ) demonstrated rapid and durable serum IgG and pathogenic autoantibody reductions, which may be therapeutic across a broad range of autoantibody-mediated immune disorders including SLE. This abstract describes the protocol of a Phase 2 study evaluating efficacy and safety of nipocalimab in patients with active SLE (NCT04882878 ). Methods: This is a phase 2, multicenter, randomized, placebo-controlled, double-blind, parallel-group study enrolling adults with active, autoantibody-positive SLE with an inadequate response to ≥1 standard of care (SoC) treatments. The study consists of a ≤6-week screening period, a 52-week double-blind treatment period, and a 6-week follow-up period ( figure 1 ). Approximately 225 participants will be randomized in a 1:1:1 ratio to receive nipocalimab dose 1, dose 2 or placebo intravenously every 2 weeks through Week 50. Results: The primary efficacy endpoint is the percentage of participants achieving an SLE Responder Index (SRI)-4 composite response at Week 24. Secondary efficacy endpoints assessed at Week 24 include the percentage of participants achieving: ≥50% reduction in Cutaneous Lupus Erythematosus Disease Area and Severity Index Activity score (CLASI), ≥50% reduction in active joints, ≥4 points improvement in SLE Disease Activity Index 2000 (SLEDAI 2K), and British Isles Lupus Assessment Group Composite Lupus Assessment response (BICLA); time to first disease flare; and reduction in corticosteroid use. Percentage of participants achieving an SRI-4 composite response at Week 52 will also be assessed. Safety endpoints include adverse events (AEs), serious AEs, AEs of special interest (severe infections, grade ≥3 hypoalbuminemia), and AEs leading to treatment discontinuation through Week 58. Conclusion: This ongoing phase 2 study will evaluate the safety and efficacy of nipocalimab in adults with active SLE, using multiple clinical outcome measures.